Fish oil-containing edible films with active film incorporated with extract of Psidium guajava leaves: preparation and characterization of double-layered edible film [version 2; peer review: 1 approved, 2 approved with reservations] - Tomoyuki Yoshino; Atsushi Hashimoto; Hiroyuki Harada; Yukihiro Yamamoto; Aji Sukoco (F1000Research)
The utilization of zein and gum arabic has grown in an attempt to formulate wall materials based on protein–polysaccharide complexes. This mixture provides a versatile delivery system for hydrophilic (guava leaf extract, GLE) or lipophilic (fish oil, FO) bioactive compounds, and it can be used as an edible film-forming polymer. This study was undertaken to characterize FO-containing edible films that were double-layered with a film containing GLE. Modified zein and gum arabic solutions (MG complex) were mixed at a ratio of 1:1.5 (v/v), adjusted to pH 5, added with glycerol (20% of the complex) and FO (5% of the complex), and finally adjusted to pH 5. This was prepared as the bottom/lower layer. The upper/active layer was prepared by mixing MG complex, glycerol, and GLE (1, 3, and 5% w/v of the complex). The total phenolic and flavonoid contents in GLE were 15.81 mg GAE/g extract and 6.99 mg QE/g extract, respectively. The IC50 of the DPPH radical scavenging activity of GLE was 26.86 ppm with antibacterial activity against Bacillus subtilis and Escherichia coli of 9.83 and 12.55 mm. The total plate counts of double-layered films containing GLE were retained below 3 log CFU/g during 28-day storage. The peroxide values of these films were dimmed for no more than 9.08 meq/kg sample on day 28 of storage. Thickness (872.00-971.67 μm), water vapor transmission rate (12.99-17.04 g/m2/day), tensile strength (1.56-2.02 kPa), elongation at break (61.53-75.41%), glass transition (52.74-57.50°C), melting peak (131.59-142.35°C), inhibition against B. subtilis (33.67-40.58 mm), and inhibition against E. coli (2.05-9.04 mm) were obtained by double-layered films. GLE can be successfully incorporated into the active layer of a double-layer film to improve its characteristics while significantly slowing down the microbial contamination and oxidation rate. MG complex and FO can also contribute to the performance of the edible film.